Hydroxyl radical enhanced carbon dots fluorescence quenching immunoassays for simultaneous detection of six kinds of antibiotics. Issue 3 (14th November 2022) - Li, Shijie; Nie, Linqing; Wen, Wenjun; Wang, Zicheng; Wang, Junping; Wang, Shuo
Abstract: Hydroxyl radical (OH)‐sensitive carbon dots (CDs) with an excitation wavelength of 390 nm and emission wavelength of 525 nm were synthesized by microwave in one‐step. Using CDs as fluorescent probes, an OH‐enhanced fluorescence quenching detection signal based on horseradish peroxidasecatalyzed H2 O2 was introduced on the basis of enzyme‐linked immunoassay, and a OH‐enhanced label‐free fluorescence quenching immunoassay (FQIA) was constructed for high‐sensitivity detection of six broad‐spectrum antibiotics. When used for nitrofuran Q2 metabolites (3‐amino‐1, 3‐oxazolidin‐2‐one, 3‐amino‐5‐(morpholin‐4‐ylmethyl)‐1, 3‐oxazolidin‐2‐one, 1‐aminohydantoin hydrochloride, semicarbazide hydrochloride), chloramphenicol (CAP) and florfenicol (FLR) detection, FQIAs achieved high sensitivity detection of 0.061, 0.0058, 0.064, 0.045, 0.015, and 0.01 ng/ml, respectively. Compared with ELISA, the detection sensitivity was improved by 2.03‐ to 7.8‐fold. On this basis, the sample pretreatment methods for six targets were optimized, and the simultaneous extraction and high‐sensitivity detection of six targets were achieved. The FQIA proposed in this work improved the detection sensitivity, reduced the sample consumption and pretreatment steps, shortened the extraction time, and improved the detection efficiency, which provided support for the development and application of new immunoassay products and the development of the rapid analysis industry. Abstract : A label‐free fluorescence quenching immunoassays using hydroxyl radical‐sensitive carbon dots as fluorescence probe was established for simultaneous extraction and highly sensitive detection of six wide‐spectrum antibiotics (nitrofuran metabolites, chloramphenicol, and florfenicol) in animal‐derived food. The organic combination of OH‐sensitive CDs, high‐sensitivity fluorescence quenching immunoassays, and efficient pretreatment methods provides support for the development and application of new immunoassay technology.